Numerical investigation on assessing the influence of diverse-shaped hybrid nanofluids on thermal performance of triple tube heat exchanger - Gaur S.K.; Sahoo R.R.; Sarkar J. (My University, 2025)
The present study explored the effects of hybrid nanofluids, composed of water-based nanoparticles in various shapes (MWCNT-cylindrical, Al2O3-blade, Graphene-platelet, and Fe3O4-brick), within a triple concentric tube heat exchanger (TCTHX). Theoretical and computational modeling was conducted for the flow of hot water and hybrid nanofluids at varying inner annulus mass flow rates (0.1 kg/s to 0.5 kg/s and at a fixed temperature of 70 °C) in the TCTHX; their influence was analyzed by the energetic and exergetic performance and revealing the findings to enhance the heat transfer efficiency. The key finding of the work is that the thermal performance factor (TPF) of the brick-blade hybrid nanofluid in the TCTHX is 4.26, which is the maximum as compared to brick-platelet, brick-cylindrical, blade-platelet, blade-cylindrical, and platelet-cylindrical hybrid nanofluids for all mass flow rates. The brick-blade hybrid nanofluid is the most economical in the TCTHX system, followed by the brick-cylindrical hybrid nanofluid. Overall, the combination of brick-blade hybrid nanofluid performs best in the TCTHX system in terms of performance index, TPF, and CBR. Brick-platelet hybrid nanofluid is 7.20% less efficient than water at a mass flow rate of 0.1 kg/s. Platelet-cylindrical hybrid nanofluid exhibits 12.71% and 5.09% lower heat transfer rate and performance index than delaminated (DI) water at the lowest mass flow rate in the TCTHX system. Brick-platelet hybrid nanofluids show a reduced Nusselt number ratio for the tested mass flow rates. Entropy generation in blade-platelet hybrid nanofluid is 19.49% lower than in (DI) water. © 2024 Elsevier B.V.